Response of citrus hybrids to Alternaria alternata inoculation - da Costa, Gabriela; Curtolo, Maiara; Magni, Thaís Cavichioli; Cristofani-Yaly, Mariângela (Comunicata Scientiae, 2020)
Citrus orchards have some limitations, such as the occurrence of phytosanitary problems. Alternaria brown spot (ABS) is caused by fungus Alternaria alternata, which affects several parts of the plant by producing a host-specific toxin, known as ACT. ABS is a limiting factor in orchards due to the susceptibility of most planted cultivars: ‘Murcott’ tangor and ‘Ponkan’ tangerine. The selection of varieties resistant/tolerant to the disease has economic importance. Therefore, the aim of this experiment was to evaluate the response to A. alternata inoculation in a population of ‘Murcott’ tangor vs ‘Pera’ sweet orange hybrids. Leaves of 2-3 centimeters in length of ‘Murcott’ tangor, ‘Pera’ sweet orange, ‘Ponkan’, ‘Dancy’, ‘Fremont’ tangerine and 198 hybrids were collected. For in vitro inoculation, monosporic A. alternata culture at concentration of 105 conidia mL-1 was used. Inoculated leaves were stored in humid chamber. After 24, 48 and 72 hours of inoculation, leaf lesions were evaluated following a diagrammatic scale. The results obtained showed that most hybrids from the crossing of ‘Murcott’ tangor vs ‘Pera’ sweet orange are susceptible to ABS. However, 44 are resistant and ten are tolerant. Among ABS-tolerant hybrids, some have phenotype similar to that of cultivated and commercialized hybrids.